DAMPAK MANAJEMEN LABA PADA ARUS KAS DAN UKURAN PERUSAHAAN TERHADAP RELEVANSI AKUNTANSI - Isro’ah, Binti; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This study aims to determine the effect of net cash flow, size of the company which is moderated by therelevance of accounting earnings management. The object of this study is a manufacturing companythat is registered in the PT. Indonesia Stock Exchange as many as 93 companies out of 143 companies,in this case the data used in the form of financial statements of 2009 to 2013. This study uses aquantitative approach. Research using statistical hypothesis testing tool to infer a causal hypothesisthat use testing (causal hypothesis). The sampling technique was done by purposive sampling. Thedata is taken from secondary data. Data analysis was performed with the aid of a computer programSPSS (Statistical Package for Social Sciences). Based on the results of the analysis show that there is apartial effect and positive net cash flow variables and the size of the company to the relevance ofaccounting (stock price). While the presence of earnings management as moderating variables canimprove the effect of firm size on stock prices but are not able to increase net cash flow effect on stockprices.Keyword : the relevance of accounting, the size of the company, the net cashflow, earnings management